Chronic Open Infective Lateral Malleolus Bursitis Management Using Local Rotational Flap. (17th September 2017) - Lee, Yong-Beom; Kim, Dae-Hwan; Jung, Jong-Ho; Park, Jae-Yong
Abstract : Background. Using a sinus tarsi rotational flap is an uncommon approach to treating chronic open infective lateral malleolus bursitis. Methods. We treated eight patients, including six males, using this approach. First, we debrided all the infected tissues and used a negative pressure wound closure system where needed. After acute infection had been controlled, the local rotational flap was used for cases where the wound could not be closed by a simple suture or bone exposure. The rotational flap was detached with a curved skin incision at the sinus tarsi next to the open wound and sutured to the defect, paying careful attention to the superficial peroneal nerve. The donor site was managed with a split-thickness skin graft. Results. The patients' mean age was 74.1 years. Six patients had a wound after suppurative infection, but two patients had ulcer-type bursitis. Six patients demonstrated full flap healing, but two patients had venous congestion necrosis. Conclusion. A sinus tarsi rotational flap is a useful method to ensure healing and coverage of chronic open lateral malleolus bursitis, especially for small to medium wounds with cavity and bone exposure.